Medisinsk fødselsregister i yrkesepidemiologisk forskning - Ågot Irgens; Karl-Christian Nordby; Petter Kristensen (Norsk Forening for Epidemiologi, 2007)
The aims of the Medical Birth Registry of Norway (MBR) are research as well as health management. By the establishment of MBR in 1967 we got a unique opportunity to study birth outcomes related to occupational exposure during a long time period and within groups. It is a virtue that MBR has registered information on all births, however, a disadvantage is that information on early spontaneous abortions and waiting time to pregnancy are missing. MBR data were linked to occupational data from other sources in published epidemiological studies related to occupation. Such sources are occupational cohorts, lists from labour unions and public registries as agricultural and horticultural censuses and population censuses. The former studies are reviewed, focusing on the definition of occupation and occupational exposure. We discuss challenges in future occupational epidemiological studies and point out some future challenges and ways to improve quality and validity. We have further emphasised on potentials in occupational epidemiology using MBR, as well as on sources where occupation and occupational exposures can be found, geneworking environment interaction studies and studies where we allow for grandmothers' working environment as well. In spite of problems attached, in Norway we have the possibilities to carry out such studies due to expansion of Norwegian systems of surveillance, and since the knowledge in biotechnology internationally is growing. This, in addition to extensive co-operation between the Nordic countries may be a useful approach in future studies.